The Detrimental Effect of Thyroiditis on Pregnancy Outcome of Patients Affected by Autoimmune Diseases: An Open Question - Botta, Angela; Rizzo, Francesca; Antonielli, Tatiana; Ciliberti, Alessandra; Garufi, Ester; Lanzone, Antonio; Garufi, Cristina; De Carolis, Sara (Frontiers in Pharmacology, 2022)
Few data are available evaluating obstetrical outcome when thyroiditis coexist with autoimmune diseases. Objectives of our study were: 1) To assess the prevalence of thyroiditis in pregnant women with autoimmune diseases 2) To evaluate the effects on pregnancy outcome when different autoimmune diseases are associated with thyroiditis. Two groups of pregnant women were analysed: a study group of pregnant women with autoimmune diseases (n=268) versus a control group of pregnant women (n=1150). In both groups the research for thyroid antibodies, anti-thyroid peroxidase antibodies and anti-thyroglobulin antibodies, was performed. The positivity had a prevalence of 17.54% in women with autoimmune diseases (n=47) versus 5.57% in the control group (n=64) (p-value <0.00001). Only major rheumatic diseases (MRD) were analysed for pregnancy outcome (week of delivery, birth weight and birth weight percentile): systemic lupus erythematosus (SLE) n=36, antiphospholipid syndrome (APS) n=44 and connective tissue diseases (CTD) n=23. MRD were divided according to positive or negative results for thyroid antibodies. Thyroiditis in CDT patients showed a detrimental effect on pregnancy outcome, in terms of earlier week of delivery: 37.86 ± 0.90 (mean ±SD) in CTD with thyroiditis versus 38.56 ± 0.73 (mean ±SD) in CTD without thyroiditis (p-value = 0.03) and lower birth weight: 2790.71g ± 257.17 SD in CTD with thyroiditis versus 3019.33g ± 305.48g in CTD without thyroiditis (p-value <0.05). In SLE and APS thyroiditis did not appear to influence pregnancy outcome. However, we suggest investigating anti-thyroid antibodies in all autoimmune diseases with special attention to pregnant women with thyroiditis and CTD.